Pengaruh Prenatal Gentle Yoga terhadap Penurunan Nyeri Pinggang Bawah pada Ibu Hamil Trimester III - Ratih Widya Wati Gultom (STIKES Columbia Asia Medan, 2024)
Prenatal gentle yoga (yoga during pregnancy) is a type of modification of hatha yoga which is adapted to the conditions of pregnant women. Some discomforts in the third trimester in pregnant women include frequent urination 50%, vaginal discharge 15%, constipation 40%, flatulence 30%, swelling in the legs 20%, cramps in the legs 10%, headaches 20%, striae gravidarum 50%, hemorrhoids 60%, shortness of breath 60% and back pain 70%. The aim of the research was to see whether there was an effect of Prenatal Gentle Yoga on reducing complaints of lower back pain in third trimester pregnant women. The conclusion of the Wilcoxon test results shows that 0.000 < 0.05, meaning that there is an acceptable effect of prenatal gentle yoga on lower back pain in third trimester pregnant women. It is hoped that pregnant women will take part in prenatal gentle yoga classes with prenatal gentle yoga facilitators who have undergone training and received certificates so that they can apply prenatal gentle yoga which is useful for reducing maternal complaints during pregnancy, including lower back pain.